Low incidence of factor VIII inhibitors in previously untreated patients with severe haemophilia A treated with octanate®: Final report from a prospective study. Issue 2 (3rd January 2018) - Klukowska, A.; Komrska, V.; Vdovin, V.; Pavlova, A.; Jansen, M.; Lowndes, S.; Belyanskaya, L.; Walter, O.; Laguna, P.
Abstract : Introduction: Octanate ® is a human, plasma‐derived, von Willebrand factor‐stabilized coagulation factor VIII (FVIII) concentrate with demonstrated haemostatic efficacy in previously treated patients with haemophilia A. Aim: This prospective, open‐label study aimed to assess the immunogenicity of octanate ® in previously untreated patients (PUPs). Methods: The study monitored development of FVIII inhibitors in 51 PUPs. Tolerability, viral safety, FVIII recovery and efficacy of octanate ® for the prevention and treatment of bleeds and in surgical procedures were also assessed. Results: Five (9.8%) of the 51 patients developed inhibitors during the study, 4 of which (7.8%) were high titre. Three inhibitor cases (5.9%) were considered clinically relevant; 2 were transient inhibitors that disappeared during regular octanate ® treatment without a change in dose or treatment frequency. Amongst 45 patients with FVIII:C <1% at baseline and who received ≥20 exposure days (EDs) or had <20 EDs but developed an inhibitor, inhibitor incidence was 11.1% (6.7% clinically relevant). All clinically relevant inhibitors developed within 20 EDs of on‐demand treatment. No inhibitors developed in PUPs receiving prophylaxis. All patients who developed inhibitors had either intron 22 inversions or large deletions. Irrespective of the reason for administration, haemostatic efficacy was rated as "excellent" in 99.6% of all infusions (4700 of 4717 infusions), and no complications were reported in 23 surgical procedures. Mean incremental in vivo recovery was 2.0%/IU/kg (±0.7) and 1.9%/IU/kg (±0.5) for the first and second assessments, respectively. Tolerability was rated "very good" in 99.9% of infusions. Conclusion: In PUPs with severe haemophilia A, octanate ® demonstrated haemostatic efficacy with a low rate of inhibitor development.